Conservation Bioethics between the Rights of Local Communities and Global Responsibility in Combating Ivory Trafficking - Dragomir, Andreea-Nicoleta; Bulea, Iulia; Florescu, Ioana (Studia Ecologiae et Bioethicae, 2026)
Once seen mainly as a trade in ivory, the killing of elephants has grown into something much larger - an ecological crisis with deep bioethical implications. This article examines how international conservation regimes, particularly CITES and the EU, impact African rural communities, which often bear most of the costs. Using case studies from Southern Africa, this study examines how reactive conservation, poor implementation of anti-poaching measures, and corruption have contributed to the penetration of international criminal interests into African spaces, while democracy is challenged as rural actors are systematically marginalised from political processes. The research question concerns the ethical legitimacy of conservation policies that impose restrictive prohibitions without equitable mechanisms for participation and compensation. The thesis advanced is that bioethics offers a normative framework capable of reconciling ecological imperatives with social justice, through the principle of shared responsibility. At the European level, Regulation (EC) No. 338/97 and the EU Action Plan against Wildlife Trafficking position the Union as a global leader, but risk reproducing normative paternalism if they ignore local autonomy. The article concludes that a bioethical framework based on shared responsibility—local, regional and global—is essential to ensure that conservation becomes a project of solidarity, justice and ecological integrity, rather than an imposed burden.